Gender equality index: main findings (Luxembourg, 2014)
"Equality between women and men is a fundamental value of the European Union, enshrined in its Treaties, including the Charter of Fundamental Rights of the European Union. The capacity of EU institutions to help shape gender relations in its Member States has been present since its earliest days (Verloo and Lombardo, 2007). Although the Treaty of Rome was signed at a time when the gender equality landscape looked substantially different from the contemporary one, it nevertheless contained a clause on equal pay between women and men, a precursor to the legislation and policy approaches that emerged throughout Europe in later years. Gender equality is recognised as vital to economic growth, prosperity and competitiveness, as exemplified by the Council’s commitment to fulfil EU ambitions on gender equality through the adoption of the European Pact for Gender Equality (2011–2020) (7349/11) and the European Commission’s Strategy for Equality between Women and Men (2010–2015) (COM(2010) 491 final). The EU, as a multi-level governance framework, plays a crucial role in enabling a concern for gender equality in Member States’ policies, gender norms and cultures to filter down from the international and EU level to national, regional and local levels."